(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
Coconut is known as a plant that can produce fruit, one of which can produce sugar which is known as palm sugar or coconut sugar. Coconut sugar is produced from the evaporation of coconut tree sap. Coconut sugar is a very popular commodity and is widely used by the community including it can be used as a mixture in processed foods. The purpose of this study was to determine the level of consumer satisfaction with coconut sugar products. The place of research was conducted in Sidomulyo Village, East Wasile District, East Halmahera Regency with the sampling method using the Accidental Sampling method, namely every consumer who came to buy coconut sugar products was sampled. The variables to be measured or observed in this study are price, taste, color, size and consumer satisfaction. Methods of data analysis using the Customer Satisfaction Index (CSI) and Importance Performance Analysis (IPA). The results of this study indicate that the measurement of the level of consumer satisfaction of coconut sugar products in Sidomulyo Village obtains a Customer Saticfactions Index (CSI) value of 66.24% which is in the range of 66 - 80 so that it is included in the satisfied category. in the "satisfied" category